Regulating the protection of women during armed conflict against sexual violence and torture / Norhalijah Yusoff … [et al.] - Yusoff, Norhalijah; Razlan, Safwah; Ahmad, Ummu Naqibah; Ahmad Shaharuddin, Siti Nuradiba (2013)
Throughout time no matter where the location, rape, torture and other acts of sexual violence towards women have always been a part of war. Regardless of, rape warfare has become an acceptable by-product for what men do even though the Geneva Conventions, the legal framework outlining the rules of war, prohibits it. Rape, torture and sexual violence went beyond from being a by-product of war to instead become a tool of war itself: a strategic military plan for genocide. Hence, this research paper will be dealing with the topic of international law by focusing on the protection of women during armed conflict against sexual violence and torture. There is inadequate protection for women during armed conflict by the international conventions, which is unable and insufficient to protect the women who became victims of sexual violence and torture. This paper will identify, analyze and compare the laws regarding sexual violence and torture during armed conflict with other international convention and treaties. Next , we will propose and recommend the amendment of the Penal Code to include a provision to protect women during armed conflict and post conflict in Malaysia by imposing tougher punishment to prosecute those accountable for committing sexual atrocities and torture and in doing so send a strong message that acts of violence towards women will not be tolerated.